The Urgency of Financial Technology Literacy for the Community - Eprianti, Nanik; Srisilawati, Popon; Ibrahim, Mohamad Andri; W, Intan Manggala (KnE Social Sciences, 2024)
Information technology-based money lending services are considered to have contributed to the development and the national economy. Financial technology (Fintech) refers to the definition of the National Digital Research Center (NDRC), namely financial innovation in the scope of financial services, combining finance and modern technology. However, the 2022 OJK survey results illustrate that only 10.9% of people use digital financial technology platforms, which is very low compared to other financial institutions. This shows the lack of literacy regarding financial technology in society. Firstly, this research aims to increase financial technology literacy for the community (MSMEs), and secondly to protect financial technology users in the community (MSMEs). This study uses a qualitative method with a descriptive analysis approach. The results of the study show steps to increase literacy according to POJK Number 77/POJK.01/2016 the scope for increasing financial literacy includes planning and implementation of: 1. Financial education; and 2. Development of infrastructure that supports financial literacy for consumers and/or the public, and protection for users of technology-based money lending services as follows; a. transparency; b. fair treatment; c. reliability; d. data confidentiality and security; and e. settlement of user disputes in a simple, fast, and affordable way. Keywords: financial technology, literacy, society